2018
DOI: 10.1155/2018/8676708
|View full text |Cite
|
Sign up to set email alerts
|

Bricks and Concrete Wastes as Coarse and Fine Aggregates in Sustainable Mortars

Abstract: The total substitution by volume of natural coarse calcareous aggregate by coarse recycled brick aggregate (RBA) and coarse recycled concrete aggregate (RCA) has been investigated to produce more sustainable and environment-friendly mortars. Aggregates were also partially substituted by their fines at 12.5% by volume. Mortars have been tested in terms of mechanical, microstructural, and durability properties. Results show that it is feasible to replace a natural calcareous aggregate entirely by recycled aggreg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 50 publications
0
17
0
2
Order By: Relevance
“…is confirmed that brick aggregates did not reduce the strength of mortar with the levels used. Moreover, Mobili et al [48] discovered that mortar with RBAs exhibited the highest amount of water absorbed by the capillary action.…”
Section: Mechanical Properties Of Mortars With Clay Brick Wastementioning
confidence: 99%
“…is confirmed that brick aggregates did not reduce the strength of mortar with the levels used. Moreover, Mobili et al [48] discovered that mortar with RBAs exhibited the highest amount of water absorbed by the capillary action.…”
Section: Mechanical Properties Of Mortars With Clay Brick Wastementioning
confidence: 99%
“…The achievement of Green Building must see the use of more efficient materials or better still of ones recovered from waste that would generally end up in landfills. It has been shown that the potential of mortars obtained by aggregates based on coarse recycled brick/concrete instead of natural ones can be a solution to avoid the depletion of natural resources and the disposal of waste material (SDG 15) [ 64 ]. Some researchers have investigated recycling automotive shredder residues and using the non-metallic fraction mixed with concrete, a lightweight aggregate with good mechanical properties is obtained [ 65 ].…”
Section: Sustainable Materials Developed By the Instm Consortiummentioning
confidence: 99%
“…Furthermore, brick aggregates have higher water absorption and lower strength than the most widely used gravel/stone aggregate, hence serving as the major problem in achieving desirable properties of concrete [ 4 , 5 ]. Finding an alternative to natural aggregates with good quality could be the best option for producing new concrete and maintaining the demand for the future.…”
Section: Introductionmentioning
confidence: 99%